Setting the stage for service experience: design strategies for functional services - Beltagui, Ahmad; Candi, Marina; Riedel, Johann Christian Karl Henry (Emerald, 2016)
Purpose:This research identifies service design strategies to improve outcome-oriented services by enhancing consumers’ emotional experience, while overcoming customer variability. Design/methodology/approach:An abductive, multiple-case study involves 12 service firms from diverse online and offline service sectors. Findings: Six service design strategies represent two overarching themes: Customer empowerment can involve design for typical customers, visibility, and community building, while customer accommodation can involve design for personas, invisibility, and relationship building. Using these strategies helps set the stage for a service to offer an emotional experience. Research limitations/implications:The study offers a first step toward combining investigations of service experience and user experience. Further research can strengthen these links. Practical implications:The six design strategies described using examples from case research offer managerial recommendations. In particular, these strategies can help service managers address the customer-induced variability inherent in services. Originality/value:Extant studies of experience staging have focused on particular sectors such as hospitality and leisure; this study contributes by investigating outcome-focused services and identifying strategies to create unique experiences that offset variability. It also represents a rare effort to combine research from service management.